2020
DOI: 10.1001/jama.2020.16349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remdesivir vs Standard Care on Clinical Status at 11 Days in Patients With Moderate COVID-19

Abstract: IMPORTANCE Remdesivir demonstrated clinical benefit in a placebo-controlled trial in patients with severe coronavirus disease 2019 (COVID-19), but its effect in patients with moderate disease is unknown. OBJECTIVE To determine the efficacy of 5 or 10 days of remdesivir treatment compared with standard care on clinical status on day 11 after initiation of treatment. DESIGN, SETTING, AND PARTICIPANTS Randomized, open-label trial of hospitalized patients with confirmed severe acute respiratory syndrome coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,411
6
46

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,159 publications
(1,498 citation statements)
references
References 17 publications
35
1,411
6
46
Order By: Relevance
“…The screening process was shown in figure 1 and 3860 studies were identified according to the research strategy initially. In total, 22 studies containing 12795 patients were adopted in our study and all of them were published in English 10,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Among trails included, half of them were RCTs, and the other were Non-RCTs.…”
Section: Literature Researchmentioning
confidence: 99%
“…The screening process was shown in figure 1 and 3860 studies were identified according to the research strategy initially. In total, 22 studies containing 12795 patients were adopted in our study and all of them were published in English 10,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Among trails included, half of them were RCTs, and the other were Non-RCTs.…”
Section: Literature Researchmentioning
confidence: 99%
“…One study reported the median time (in days) to reach a NEWS2 score of zero [23] ( Table 2). The study published by Spinner [8] also reported clinical improvement at days 7, 14, and 28, but it is not declared which scale was used to assess the clinical improvement.…”
Section: Clinical Improvementmentioning
confidence: 99%
“…In this review, the data were extracted from nine studies reporting any severe adverse events [8][9][10]18,19,[21][22][23]26] (It must be noted that a patient can develop one or more than one adverse event). Severe (or serious) adverse events were extracted as dichotomous data (Table 2).…”
Section: Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations